2020
DOI: 10.3389/fneur.2020.00494
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stability and Trunk Control Improvements Following Robotic Balance and Core Stability Training in Chronic Stroke Survivors: A Pilot Study

Abstract: Stroke survivors show greater postural oscillations and altered muscular activation compared to healthy controls. This results in difficulties in walking and standing, and in an increased risk of falls. A proper control of the trunk is related to a stable walk and to a lower falling risk; to this extent, rehabilitative protocols are currently working on core stability. The main objective of this work was to evaluate the effectiveness of trunk and balance training performed with a new robotic device designed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 85 publications
2
65
0
1
Order By: Relevance
“…Pessoas com diferentes condições de saúde como: AVC, Doença de Parkinson, Esclerose Múltipla, entre outras, apresentam maiores oscilações posturais e ativação muscular alterada em comparação com controles saudáveis, o que resulta em dificuldades para andar e ficar em pé, além de maior risco de quedas [17][18][19] . Em relação aos métodos de avaliação de equilíbrio, estes são úteis para ajudar os profissionais a determinar o plano de reabilitação personalizado adequado para seus pacientes e a escolha deve ser apropriada ao contexto e população de interesse 20 .…”
Section: Discussionunclassified
“…Pessoas com diferentes condições de saúde como: AVC, Doença de Parkinson, Esclerose Múltipla, entre outras, apresentam maiores oscilações posturais e ativação muscular alterada em comparação com controles saudáveis, o que resulta em dificuldades para andar e ficar em pé, além de maior risco de quedas [17][18][19] . Em relação aos métodos de avaliação de equilíbrio, estes são úteis para ajudar os profissionais a determinar o plano de reabilitação personalizado adequado para seus pacientes e a escolha deve ser apropriada ao contexto e população de interesse 20 .…”
Section: Discussionunclassified
“…At the conclusion of the study, their athletic and living ability significantly improved [ 21 ]. Another reports that chronic stroke hemiplegia patients receiving three months of robotic training had improvements in proprioceptive control, reactive balance, and posture control [ 22 ]. However, a systematic review and meta-analysis found that although RT has the benefit of low labor cost, when the same amount of RT is employed as conventional treatment, RT alone is not better than conventional treatment [ 23 ].…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%
“…Core stability delivers a significant part in upgrading function and alleviating weight bearing at the joints whilst doing various assignments. [31][32][33][34][35] The core, which lies in lumbar area, needs to be sturdy the whole time as its function to hold the lumbar area stable and at the same time It is important that the lumbar spine formed a rigid cylinder to augment stiffness of the lumbar spine by core muscle contraction. Another principal aspect to note is that the oblique abdominal and rectus abdominis muscles are behaved in direction-specific patterns with regards to limb motion.…”
Section: Postural Control Rehabilitation Principlesmentioning
confidence: 99%